SUICIDAL NARRATIVE IN KATHLEEN GLASGOW’S GIRL IN PIECES - Anita Melati; Rachmat Nurcahyo (Universitas Negeri Yogyakarta, 2024)
This research breaks down into two main goals: first, it aims to reveal the suicidal acts of the characters in Kathleen Glasgow's Girl in Pieces; second, it will examine the way in which the characters' suicidal narrative is constructed. The Sigmund Freud psychoanalytic theory and narratology were employed in this study to address the research objectives. Girl in Pieces, a novel by Kathleen Glasgow, serves as the data source for this qualitative investigation. This study demonstrates how the interaction between outside factors and internal conflicts illuminates the reasons behind suicide. The presence of ambivalent emotions, the impact of the superego's influence, and the regular reaction of loss to the withdrawal of libido caused the complex five characters to experience melancholy and mourning. This condition demonstrates how the novel's suicidal narrative is represented by the characters' psychological suffering. The manifestation of melancholy and its effects highlight the crucial role the superego plays in encouraging self-destructive behavior. The superego functions as a metaphorical